2012
DOI: 10.1016/j.brat.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of maladaptive beliefs in cognitive-behavioral therapy: Evidence from social anxiety disorder

Abstract: Beliefs that are negatively biased, inaccurate, and rigid are thought to play a key role in the mood and anxiety disorders. Our goal in this study was to examine whether a change in maladaptive beliefs mediated the outcome of individual cognitive-behavioral therapy (CBT) for social anxiety disorder (SAD). In a sample of 47 individuals with SAD receiving CBT, we measured maladaptive interpersonal beliefs as well as emotional and behavioral components of social anxiety, both at baseline and after treatment compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 34 publications
2
56
0
1
Order By: Relevance
“…Intervening variables form the basis of many psychological theories and are of particular interest in clinical treatments and interventions. Despite some research on maladaptive self-beliefs and beliefs about social situations in SAD (Boden et al, 2012;Foa, Franklin, Perry, & Herbert, 1996;Hofmann, 2004;Rapee et al, 2009), to date, there has been very little work on people's beliefs about their emotions. This is unfortunate because there is good reason to believe emotion beliefs may have clinical significance (Hofmann, 2000(Hofmann, , 2005(Hofmann, , 2007Tamir & Mauss, 2011).…”
Section: Cognitive Variables In Social Anxiety Disordermentioning
confidence: 97%
See 1 more Smart Citation
“…Intervening variables form the basis of many psychological theories and are of particular interest in clinical treatments and interventions. Despite some research on maladaptive self-beliefs and beliefs about social situations in SAD (Boden et al, 2012;Foa, Franklin, Perry, & Herbert, 1996;Hofmann, 2004;Rapee et al, 2009), to date, there has been very little work on people's beliefs about their emotions. This is unfortunate because there is good reason to believe emotion beliefs may have clinical significance (Hofmann, 2000(Hofmann, , 2005(Hofmann, , 2007Tamir & Mauss, 2011).…”
Section: Cognitive Variables In Social Anxiety Disordermentioning
confidence: 97%
“…that one is unattractive or perceived as 'boring') (Rapee, Gaston, & Abbott, 2009), and the role of negative interpersonal beliefs (e.g. the belief that one is 'unlovable' or 'doesn't fit in') (Boden et al, 2012).…”
Section: Cognitive Variables In Social Anxiety Disordermentioning
confidence: 99%
“…Mediator analyses have begun to identify specific mediators of the impact of CBT for SAD on social anxiety symptom reduction. A recent randomized controlled trial of CBT for SAD has shown that reductions of maladaptive interpersonal beliefs [69] as well as increases in cognitive reappraisal selfefficacy [70•] and positive self-views [71] during treatment mediate reductions in social anxiety symptoms. Importantly, increases in cognitive reappraisal self-efficacy [70•] and positive self-views [71] also predict reduction of social anxiety symptoms 1-year post-CBT.…”
Section: Cognitive Behavioral Therapymentioning
confidence: 99%
“…Because there was not any study on combined aspects of cognition, metacognition and behavioral, therefore similar research was mentioned in explaining the results. Similar research in this area include Boden et al (2012), Wells and Carter (2001), Mahjuob and Teymouri (2015), Ghahvehchi et al (2015), Bahadori et al (2012), and Salmani et al (2014).…”
Section: Discussionmentioning
confidence: 67%
“…Different methods have been used to relief meta-worry beliefs. These proven-effective methods comprised cognitive therapy (Boden, John, Goldin, Werner, Heimberg & Gross, 2012;Wells & Carter, 2001;Ghahvehchi, Fathi Ashtiani & Satkin, 2015;Mahjuob & Teymouri, 2015), metacognitive therapy (Bahadori, Jahanbakhsh, Kajbaf & Faramarzi, 2012;Salmani, Hasani, MohammadKhani & Karami, 2014), LEARN multifaceted intervention (Mousavi, Alipour, Zare, Agah Heris & Janbozorgi, 2014), and attention training technique (Sheykhan, Mohammadkhani & Hasanabadi, 2013).…”
Section: Introductionmentioning
confidence: 99%